2019
DOI: 10.1039/c9ra06047b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and spectroscopic responses of pH-sensitive nanoparticles: influence of the silica matrix

Abstract: Self-calibrating, fluorescent nanoparticles with diameter far below 50 nm are synthesized with embedding a new ratiometric and pH sensitive indicator dye. The prompt response of the fluorophore allows for determining the intracellular pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…In this context, Finlayson et al demonstrated that, above the T g , the poly(ethylacrylate) (PEA) shell shows viscoelastic properties with a corresponding shear rate of η = 10 3 –10 4 Pa·s at 100 °C, which is important for the ordering process [ 37 ]. Moreover, protic polar environments turned out to enhance ESPT [ 29 , 30 ]; therefore, it is necessary to include hydroxylic moieties into the shell material. Furthermore, it can be assumed that, the higher the content of the hydroxylic groups in the copolymer, the higher the corresponding hydrophilicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Finlayson et al demonstrated that, above the T g , the poly(ethylacrylate) (PEA) shell shows viscoelastic properties with a corresponding shear rate of η = 10 3 –10 4 Pa·s at 100 °C, which is important for the ordering process [ 37 ]. Moreover, protic polar environments turned out to enhance ESPT [ 29 , 30 ]; therefore, it is necessary to include hydroxylic moieties into the shell material. Furthermore, it can be assumed that, the higher the content of the hydroxylic groups in the copolymer, the higher the corresponding hydrophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the excitation spectrum exclusively shows a band at 447 nm, which is assigned to ROH. Although the extent of emission of the conjugated base of the photoacid is minor, its observation unambiguously points to ESPT [ 30 ]. Summarizing, PHEMA- and PIPGMA-containing opal films spectra show evidence for ESPT, which was confirmed for a PGMMA-containing film by adding water (pH 3.5) as proton acceptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The change of the solvent should effect the spectra of the dyes on the surface, while particles with dyes in the interior should show no or only a minor solvent influence [47].…”
Section: Validation Of Binding Character and Dye Distribution In The Particlementioning
confidence: 99%
“…In addition to the position of the dye in the particle, the covalent or non-covalent nature of the dye-particle connection should be proven, as well as the strength of the dye-particle interaction. Due to low dye concentrations, statements about the strength of the dye binding are only possible with spectroscopic methods such as fluorescence anisotropy [47]. In this method, fluorophores get excited by polarized light.…”
Section: Validation Of Binding Character and Dye Distribution In The Particlementioning
confidence: 99%